Effects of Hydrophobic Nanospaces on Structures of Lysozyme - Koki Takenaka; Tomonori Ohaba; Kazuo Takei; Kuniko Akama; Joaquin Silvestre-Albero; Hirofumi Kanoh (Adsorption Science & Technology)
Adsorption of lysozyme on carbon nanospaces was studied by measurement of structures and biological activities of the adsorbed lysozyme. Carbon aerogel (CA) was used as the carbon material. Several kinds of CAs with different pore sizes were prepared. Porosities of CAs were characterized by a nitrogen adsorption measurement at 77 K. Adsorption measurements showed that mesopores with diameters between 15 and 25 nm were the most suitable for lysozyme adsorption. However, because the size of lysozyme is less than 5 nm in length, this adsorption behaviour suggests that lysozyme molecules may associate with one another to form clusters on mesopores of CAs. This is a unique behaviour because it is well-known that lysozyme indicates monolayer adsorption on the flat surface. The X-ray diffraction patterns of lysozyme-adsorbed CA showed a few peaks originating from the structure of lysozyme. The strongest peak of a bulk species of lysozyme was shifted by heating because of changes in its secondary structures. Lysozyme-adsorbed CA showed behaviours different from that of bulk species of lysozyme on heating. The recovery of biological activity of lysozyme denatured by heating was promoted by CA. Thus, hydrophobic mesopores of CA influence the stability of the structure of lysozyme.